Detection of RUNX2 gene expression in cumulus cells in women undergoing controlled ovarian stimulation - Papamentzelopoulou Myrto; Mavrogianni Despina; Dinopoulou Vasiliki; Theofanakis Haralampos; Malamas Fotodotis; Marinopoulos Spyros; Bletsa Ritsa; Anagnostou Elli; Kallianidis Kostas; Loutradis Dimitris (BMC, 2012)
Abstract Background RUNX2 is a transcription factor, whose expression has been recently identified in the mouse ovary. Regulation of RUNX2 expression and its function in the human ovary have not been determined yet. The aim of the present study is the investigation of the possible correlation between RUNX2 gene expression in cumulus cells and controlled ovarian stimulation and pregnancy outcomes after ART treatment. Methods A total of 41 patients undergoing ICSI treatment for male factor infertility were enrolled into a specific ART program, during which cumulus cells were collected. The expression of RUNX2 gene in cumulus cells was examined by real-time PCR. Results Concerning RUNX2 gene expression, 12 out of 41 women were detected with RUNX2 expression, with ratios ranging from 0.84 to 1.00, while 28 out of 41 women had no expression (ratio = 0). Only 1 woman presented a weak RUNX2 gene expression (ratio = 0.52). From 8 women that proceeded to pregnancy, 7 of them did not express RUNX2 gene in cumulus cells, while one was the woman with weak gene expression that also achieved pregnancy. The group of women without RUNX2 expression presented higher number of follicles (p = 0.013), higher number of retrieved oocytes (p = 0.016), higher basal LH serum levels (p = 0.016) and higher peak estradiol levels (p = 0.013), while the number of fertilized oocytes differed marginally between the two groups (p = 0.089). Moreover, RUNX2 expression was negatively associated with LH levels (OR = 0.22, p = 0.021) and E2 levels (OR = 0.25, p = 0.026). Conclusions Consequently, based on the preliminary findings of the present pilot study a potential inhibitory mechanism of RUNX2 gene is observed in the ovary when high mRNA levels are detected, suggesting that RUNX2 could possibly be used as a candidate genetic marker in the monitoring of the outcome of an ART treatment.